Early clinical predictors of fulminant myocarditis in pediatric patients: a retrospective cohort study - Yuan, Jia; Li, Ming; Ma, Li; Wu, Zonglv; Wu, Yujian; Huang, Yuping; Yin, Zongxiang; Zhou, Na (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveVarious clinical indicators can increase the likelihood of early identification of fulminant myocarditis, the identification of which is important for early treatment.MethodThe medical records of all patients (n = 269) who were diagnosed with acute myocarditis between January 2014 and December 2023 were retrospectively analyzed. Patients were divided into two groups: the nonfulminant myocarditis group (n = 229) and the fulminant myocarditis group (n = 40). Baseline demographics, laboratory findings, electrocardiograms, echocardiograms, and treatment regimens were compared between the two groups via multifactorial analysis. A receiver operating characteristic (ROC) curve was used to explore the predictive value of related factors.ResultsThe median age of patients with fulminant myocarditis was significantly greater than that in the nonfulminant group (P = 0.015). The presenting symptoms at admission varied and included fever and respiratory, digestive, and circulatory symptoms. Among them, fever and hypotension were more common in the fulminant myocarditis group (P < 0.05), and vomiting was significantly more common in the nonfulminant myocarditis group (P = 0.017). Logistic regression analysis revealed that N-terminal pro-B-type natriuretic peptide (NT-proBNP), lactate (Lac), alanine aminotransferase (ALT), cardiac troponin I (cTnI), chest distress, and hypotension were early risk factors for fulminant myocarditis. ROC curve analysis demonstrated that NT-proBNP, ALT, cTnI, and Lac can serve as predictors for the early diagnosis of fulminant myocarditis. The optimal predictive values for these markers are 2,783.5 pg/ml for NT-pro BNP, 34.5 U/L for ALT, 0.2 µg/ml for cTnI, and 3.05 mmol/L for Lac.ConclusionsThis study revealed that NT-proBNP, cTnI, ALT, and Lac can serve as predictive factors for the early identification of fulminant myocarditis. These findings emphasize the importance of early identification and timely diagnosis for improving the overall prognosis of patients.